If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-5)(4 + -5x) = 7 + -3(3x + -9) (4 * -5 + -5x * -5) = 7 + -3(3x + -9) (-20 + 25x) = 7 + -3(3x + -9) Reorder the terms: -20 + 25x = 7 + -3(-9 + 3x) -20 + 25x = 7 + (-9 * -3 + 3x * -3) -20 + 25x = 7 + (27 + -9x) Combine like terms: 7 + 27 = 34 -20 + 25x = 34 + -9x Solving -20 + 25x = 34 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -20 + 25x + 9x = 34 + -9x + 9x Combine like terms: 25x + 9x = 34x -20 + 34x = 34 + -9x + 9x Combine like terms: -9x + 9x = 0 -20 + 34x = 34 + 0 -20 + 34x = 34 Add '20' to each side of the equation. -20 + 20 + 34x = 34 + 20 Combine like terms: -20 + 20 = 0 0 + 34x = 34 + 20 34x = 34 + 20 Combine like terms: 34 + 20 = 54 34x = 54 Divide each side by '34'. x = 1.588235294 Simplifying x = 1.588235294
| 7w+21=-5(w+3) | | -3g-7=-7-2g | | 33-x=26 | | 7x+10=6x+17 | | -(x+3)+6x= | | 23-x=17 | | 9x^2-17=-16 | | -7(1+4x)=217 | | 6x+9=4x+25 | | 8-7j=-6j | | 12+1y+3y=28 | | (2x-1)/3=5x-6/4 | | 2x-9=3x+0 | | 4=-2(4.50+25p) | | -32-8x+6x=12 | | -3(w+1)-4= | | 58=3x+4x+2 | | p=5+2q | | 4=-2(4.50+25) | | 3X*2-12X=2X+7 | | 19+169r^2=380 | | 2.1x-2.16=0.84-5.4 | | 5w=6w-8 | | 5x+2x-6=43 | | 3(2u-3)-2(u+4)= | | 5p^2-17=28 | | f(x)=x-26 | | -400=8(-8b+6) | | 9(-39/2)-5((-39/2)-6) | | 5(w+6)-7w= | | 5x/5x^3 | | 9(-39/2)-5((-39/2)-6 |